Electrodeposition as an Alternative Approach for Monolithic Integration of InSb on Silicon - Hnida-Gut, Katarzyna E.; Sousa, Marilyne; Hopstaken, Marinus; Reidt, Steffen; Moselund, Kirsten; Schmid, Heinz (Frontiers in Chemistry, 2022)
High-performance electronics would greatly benefit from a versatile III-V integration process on silicon. Unfortunately, integration using hetero epitaxy is hampered by polarity, lattice, and thermal expansion mismatch. This work proposes an alternative concept of III-V integration combining advantages of pulse electrodeposition, template-assisted selective epitaxy, and recrystallization from a melt. Efficient electrodeposition of nano-crystalline and stochiometric InSb in planar templates on Si (001) is achieved. The InSb deposits are analysed by high resolution scanning transmission electron microscopy (HR-STEM) and energy-dispersive X-ray spectroscopy (EDX) before and after melting and recrystallization. The results show that InSb can crystallise epitaxially on Si with the formation of stacking faults. Furthermore, X-ray photoelectron (XPS) and Auger electron (AE) spectroscopy analysis indicate that the InSb crystal size is limited by the impurity concentration resulting from the electrodeposition process.